Filtration Systems in Fishery Aquaculture - Sugandhy, Rioaldi; Yustianti, Ayi; Nugraha, Yoga; Prananda, Rizky; Andriani, Yuli (Jurnal Media Akuakultur Indonesia, 2024)
The fisheries cultivation process requires carrying capacity to maintain water quality in order to produce maximum results in the cultivation process. Fisheries cultivation is starting to spread on a small scale (urban farming) with the aim of independent food security. This requires a solution to maintain water quality which aims to increase growth, survival and prevent unpleasant aromas from emerging from cultivation activities. Maintaining water quality can be done by using filtration or recirculation systems in cultivation activities. This scientific article uses a library research method with a qualitative descriptive approach, namely using a content analysis method. Filter media is divided into mechanical (cotton, Dacron), biological (bio ball, ceramic ring), and chemical (activated carbon, zeolite stone). The use of various types of filter media affects water quality, growth and survival of fish. Using vegetables as additional filtration also affects water quality.